Application of Transposition Procedure to the Translation of Emotive Words in Kṛṣṇa Text - I Wayan Suryasa; I Nengah Sudipa; Ida Ayu Made Puspani; I Made Netra (The Doctoral Studies Program of Linguistics of Udayana University, 2019)
The current study is aimed at investigating the application of the transposition procedure tothe translation of the emotive words found in Kṛṣṇa text. The emotive words used are based on thecognitive scenario. There are five emotive words described. They are happy, sad, fear, anger,envious, and ashamed. The transposition procedure was appplied to the replacement of one wordclass by another. There is no change in meaning. The transportation procedure can be appliedintralinguistically, referring to as particular language. The original expression is the base one and theresult is the transposed expression. The highly versatile translation procedure is transposition. Thestylistic value of the transposed expression is sometimes substantially different from the baseexpression. Transposition can render the nuance of style, and used as a main means of finetuning thestylistic elegance of the translation product.